Pengembangan Instrumen Pengukuran Kedisiplinan Siswa - Dewanti, Sintha Sih; Pramesti, Fauziah Indria; Al Hawari, Defahayu As Syaura; Hanifah, Alma Aulia (Jurnal Tadris Matematika, 2024)
Measuring student discipline is crucial because it helps create an orderly and conducive learning environment and teaches responsibility and self-control. This study aims to develop an effective non-test instrument for measuring student discipline using Exploratory Factor Analysis (EFA) and the Partial Credit Model (PCM) from Item Response Theory (IRT). The instrument was analyzed using EFA, which successfully identified five main factors corresponding to aspects of discipline: self-control, compliance (adherence to rules), concentration ability, strong determination, and responsibility. IRT analysis with the PCM model revealed that the items in the instrument had varying levels of difficulty and discrimination, with nine out of 15 items showing good discriminatory power. This instrument can provide accurate and reliable measurements of student discipline, assisting educators in identifying areas needing improvement and designing appropriate interventions to support character development. This study demonstrates that combining EFA and IRT PCM can produce a valid, reliable instrument with good discriminatory power.